Harnessing Ethiopian floodwaters helps dryland pastoralists – and the approach is being scaled up (WLE-ICRISAT) - CGIAR Research Program on Water, Land and Ecosystems (2021)
The outcome of flood spreading weirs was a fast recovery of landscapes, with 150% biomass yield increment, increased access to dry season feed and food. The productivity and landscape features have changed from an abandoned field to a productive landscape. The flood patterns and sediment loads created at least four different crop management zones and productivity levels. The major ‘agents’ were community leaders (‘Kedoh Abbobati’) who keenly debated the potential benefits and drawbacks of innovations, enforced customary rules and bylaws.